Perangkat Lunak Komputer - Agung Rizky Jamas; Destri Anggraeni; M. Aziz Nur Mubarak; Didik Aribowo (Fakultas Teknik Universitas Cenderawasih, 2023)
The development of the world of technology at this time has a major influence and impact on the development of educational information systems. In the world of information systems that aim to provide various kinds of information, and with the development of technological progress experiencing very rapid development, it is characterized by the increasing number of computer-based information systems. The objectives of this journal are (1) Analyzing the history and evolution of browsers, (2) Identifying the Challenges Faced by Browsers (3) Reviewing the Latest Innovations in software. The method in writing this journal is in the form of data collection from several journals. (1) The Internet was first created by the United States Department of Defense (DARPA) in the 1960s. Early browser software such as